Coping and Caregiving-Satisfaction among Caregivers of Patients with Cancer at the Uganda Cancer Institute and Mbarara Regional Referral Hospital in Uganda - Rachel, Kansiime; Rukundo, Godfrey Zari; Mutto, Milton; Orem, Jackson; Niyonzima, Nixon; Kizito, Simon (Open Journal of Medical Psychology, 2022)
This study aimed at investigating the relationship between coping and caregiving satisfaction among informal cancer caregivers in Ugandan referral hospitals. A convenient sample of 436 consenting informal care givers aged 18 years and above were interviewed; a cross-sectional design was used. Because of the difficulty in defining a fixed population for this category of care givers, whoever was found at the bed side meeting the inclusion and exclusion criteria were recruited into the study. A tri-dimensional coping scale (namely; problem solving, denial and venting) was used to measure coping. After controlling for all the relevant covariates (Patient’s age, sex of care giver, education of caregiver, respondent’s age, respondent’s education level, respondent’s education, respondent’s country of origin, respondent’s religion, stage of cancer, score on burnout scale), the venting aspect of coping had a significant effect on caregiving satisfaction (F = 1.83, P-value = 0.03). The above covariates accounted for 41.3% of the variability in care giving satisfaction scores (R2 = 0.413). Venting as a coping mechanism had a significant effect on caregiving satisfaction. There is need to pay attention to the coping strategies of informal cancer caregivers to enhance their care giving experience. There is need to help caregivers develop healthy coping methods as they participate in cancer care
Keywords: Coping; Caregiving Satisfaction; Cancer Givers; Uganda